Laminate comprising layered mineral material layer and polyurethane layer
By using a polyurethane layer composed of polyisocyanate and non-polar polyester polyol in the laminate, combined with a layered mineral material, the problems of large thickness, high rigidity and long curing time in the prior art are solved, and a flexible, flexible and fast curable laminate preparation is achieved.
Patent Information
- Application Number
- CN202380054550.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-07-20
- Filing Date
- 2023-07-19
- Publication Date
- 2025-03-07
AI Technical Summary
It is difficult to prepare large-area flexible slate laminates with a thickness less than 1 mm and bendability, and the preparation method has problems with long-term curing and solvent use.
Using a laminate comprising at least one layer of layered mineral material and a polyurethane layer, the polyurethane layer consisting of a polyisocyanate composition and a non-polar polyester polyol, the flexibility and rapid curing of the laminate is achieved through specific component ratios and process methods.
A bendable laminate with a thickness of less than 1 mm was successfully prepared, which shortened the curing time, reduced the use of solvents, and improved production efficiency and product performance.
Smart Images

Figure BDA0005246899150000031 
Figure BDA0005246899150000291 
Figure BDA0005246899150000301
Abstract
Description
[0001] In a first aspect, the present invention relates to a laminate comprising at least one layer of a layered mineral material and a polyurethane layer, wherein the polyurethane of the polyurethane layer is obtained or can be obtained from a mixture comprising the following components: (i) a polyisocyanate composition; (ii) a polyol composition, the polyol composition comprising (iia) at least one non-polar polyester polyol, the average electronegativity difference ΔEN of the non-polar polyester polyol is <0.38, wherein ΔEN is the sum of the electronegativity differences (δEN) of all bonds in the non-polar polyester polyol divided by the total number of bonds in the non-polar polyester polyol. A second aspect of the present invention relates to a method for preparing the laminate of the first aspect, and a third aspect relates to another method for preparing the laminate of the first aspect. In a fourth aspect, the present invention relates to a laminate obtained or can be obtained by a method according to the second or third aspect. A fifth aspect of the present invention relates to the use of the laminate according to the first aspect or the laminate according to the fourth aspect for wall panels, roof panels, facings, wallpapers, kitchen surfaces, shower enclosures, clothes, shoes, bags, automotive interior parts, battery parts, general furniture, sofas, outdoor furniture, and decorative items.
[0002] Mineral materials have properties such as surface texture, which make them very interesting for various applications. For example, slate is a layered natural stone that is often used for roofs, but is also used as a surface for living spaces. However, significant disadvantages are the weight and rigidity of the stone. Laminates comprising inorganic and polymer layers are therefore often the material of choice.
[0003] US 3,287,197 describes a method for permanently coating an inorganic surface with a plastic for a time sufficient to form a mechanical permanent surface, wherein a thermoplastic polymer is indicated as the material for the plastic. DE 19522875A1 relates to a flexible sheet having a surface layer, the surface layer comprising at least one multilayer stone, wherein the surface layer is connected to a flexible, tension-resistant carrier layer by adhesion or by bonding. Adhesion is achieved by using an adhesive synthetic resin selected from the group consisting of polyolefins, olefin polymers and copolymers, acrylate polymers, polyamides, polyesters, epoxy resins, polyurethanes and mixtures and copolymers of these substances. Regarding polyurethanes, the document only discloses that these are prepared from polyisocyanates and polyols. EP 3785 900 A1 relates to a flexible thin stone product having a stone layer and a polymer layer adjacent thereto, wherein a fibrous structure is arranged in the polymer layer. The polymer layer is formed by a 2-component polyurethane adhesive. Regarding polyurethanes, the document only discloses that the polyurethane is formed by polyols and isocyanates (PU NEUKADUR PN 9712 2-C polyurethane adhesive).
[0004] Mechanical splitting of slate blocks produces a rigid and fairly heavy stone with a thickness of at least 4 mm. Flexible slate laminates of the prior art typically have a thickness of at least 1 mm and are fairly rigid and only slightly flexible / bendable. Methods for producing at least flexible slate laminates are known, however, no information is available about the chemical nature of the polymer materials used. In addition, these methods are usually done manually and require long curing times. The polymer materials may contain solvents, so such laminates may be difficult to pass VDA278:2016-05 (Thermal Desorption Analysis of Organic Emissions for the Characterization of Non-Metallic Materials for Automotives). In particular, solvent-based polymer materials may have a flash point below 100° C., which will lead to additional safety issues and therefore require safety measures, as well as additional investment costs for production equipment. The polymer materials of the prior art may include substances that are persistent, bioaccumulative and / or toxic raw materials of great concern. In order to form a large area of extremely flexible 3D material, it is necessary to prepare a large number of hardened, rigid, overlapping, small plate-like scales and connect them loosely like the epidermis of reptiles or pangolins, for example. It is completely unknown to prepare such a material from a single oilcloth-like, extremely flexible or soft material, which would also qualify as clothing with a slate surface.
[0005] The technical problem underlying the present invention is therefore to provide a laminate and a method for producing the same which overcome the above-mentioned disadvantages and wherein the laminate should in particular have a thickness of less than 1 mm and should be bendable, while the preparation method should enable relatively short curing times to be achieved.
[0006] According to a first aspect of the invention, this problem is solved by a laminate comprising at least one layer of a laminar mineral material and a polyurethane layer, wherein the polyurethane of the polyurethane layer is obtained or obtainable from a mixture comprising:
[0007] (i) a polyisocyanate composition;
[0008] (ii) a polyol composition comprising
[0009] (iia) at least one non-polar polyester polyol having an average electronegativity difference ΔEN<0.38, wherein ΔEN is the sum of the electronegativity differences (δEN) of all bonds in the non-polar polyester polyol divided by the total number of bonds in the non-polar polyester polyol.
[0010] The laminate is preferably a flexible laminate, which means that the laminate can bend or flex or twist without breaking when a force is applied. When the force is removed, the deformation stops existing, and the laminate can return to the initial configuration. The force required to bend the laminate is so low that the laminate bends due to its own weight. In order to determine the bending (or stiffness), according to ASTM D1388 (October 2018, Cantilever Bending Length Test), the sample of the laminate is inserted into a textile stiffness tester, a weighed slide is placed on the sample and advanced at a constant rate. When the leading edge of the sample protrudes from the platform, the sample bends under its own mass. In the case of a deviation of >1cm from the horizontal line at an overhang of 20cm, the laminate is classified as flexible.
[0011] In some preferred embodiments of the laminate, the mixture comprises ≥ 8 wt% of at least one non-polar polyester polyol (iia), based on 100 wt% of the total weight of (i) and (ii).
[0012] In some preferred embodiments of the laminate, at least one non-polar polyester polyol (iia) has an average electronegativity difference ΔEN < 0.35, preferably < 0.33, wherein ΔEN is the sum of the electronegativity differences (δEN) of all bonds in the non-polar polyester polyol divided by the total number of bonds in the non-polar polyester polyol. The electronegativity difference of a bond (ΔEN, δEN) is the difference in the electronegativity of the atoms involved (i.e., atoms connected to each other by a bond). δ EN is known to those skilled in the art and is calculated for a bond based on the electronegativity of the atoms forming the bond, i.e., a smaller EN value is subtracted from a higher EN value (see also AL Allred, EG Rochow: A scale of electronegativity based on electrostatic force. "Journal of Inorganic and Nuclear Chemistry", 1958, DOI 10.1016 / 0022-1902 (58) 80003-2; AL Allred: Electronegativity values from thermochemical data. "Journal of Inorganic and Nuclear Chemistry", 1961, DOI 10.1016 / 0022-1902 (61) 80142-5). The electronegativity values of all atoms based on the Allred-Rochow scale are known to those skilled in the art and can also be obtained, for example, from the Periodic Table of the Elements (PTE).
[0013] To calculate the average electronegativity difference (ΔEN) of a complete molecule (here, a polyol), the ΔEN values of all bonds in the polyol are added together and then the resulting sum is divided by the number of bonds in the polyol, as shown in Equation (1):
[0014]
[0015] in
[0016] ΔEN is the average electronegativity difference of the polyols,
[0017] δEN is the electronegativity difference of the atoms of the bonds in the polyol (according to the Allred-Rochow scale), and n is the number of all bonds in the polyol.
[0018] For the calculation of δEN, it is irrelevant whether the bond connecting the two atoms is a single or double bond, only the difference in the electronegativity values of the atoms involved is relevant. The molecules considered typically have sp3 or sp2 carbon atoms. Therefore, the orientation of the bonds can be neglected. Cases where polar bonds are present but the overall polarity is zero due to the linear orientation of the adjacent bonds (example: CO2) are irrelevant.
[0019] Regarding ΔEN, for example, for a compound such as methyl stearate, which contains zero hydrogen-oxygen bonds (OH bonds), 3 carbon-oxygen bonds (CO bonds), 38 carbon-hydrogen bonds (CH bonds), and 17 carbon-carbon bonds (CC bonds), wherein oxygen has an electronegativity value of 3.5, carbon has an electronegativity value of 2.5, and hydrogen has an electronegativity value of 2.2, all according to PTE, ΔEN is 0.248.
[0020] There is no restriction on the non-polar polyester polyol, as long as the Δ EN of the non-polar polyester polyol is <0.38, preferably <0.35, more preferably <0.33. Methods for preparing such non-polar polyols comprising polyester units and optional polyether units are known to technicians. Non-polar (hydrophobic) polyester polyols themselves are the reaction products of at least 2-functional acids with diols or triols. During the reaction, ester bonds are formed and water is released. For example, at least 2-functional acids can be blended with monobasic acids, especially fatty acids. Alternatively, non-polar polyester polyols can be formed by transesterification reactions starting from polyester polyols (e.g., triglycerides or diglycerides of carboxylic acids) and diols or by transamination reactions starting from polyester polyols and hydroxyl functional primary or secondary amines (such as diethanolamine). Branched non-polar polyester polyols can also be obtained by transesterification reactions of polyester polyols with 3- or 4-functional polyols. Another option is the reaction of CC double bonds involving fatty acids or triglycerides or diglycerides of fatty acids. A very common way involves the reaction of epoxidized carboxylic acids or carboxylic acid derivatives with low molecular weight diols or triols, or the same reaction with triglycerides or diglycerides of carboxylic acids. In this case, ester groups are formed, and additional ring opening of the epoxy ring by the alcohol may occur to form ether bonds. One diol or triol molecule may be able to open multiple epoxy rings. The ring opening of the epoxy may be able to be carried out by water to form hydroxyl groups. Polyester polyols can be synthesized in a way that several of the reactions described can occur simultaneously.
[0021] Examples of non-polar polyester polyols are castor oil, polyols based on natural oils and modified non-polar polyester polyols. Modification reactions include oxidation of C=C double bonds, reaction with diols or triols, epoxidation of C=C double bonds, opening of alkylene oxide rings with water (hydrolysis) or alcohols (alcoholysis) (monoalcohols, diols, triols) or by catalytic hydrogenolysis, optional alkoxylation of such compounds, hydration after hydrogenation, dimerization (e.g. via Diels-Alder reaction) and transesterification. The goals of the modification are a) to form more hydroxyl groups for better incorporation into the polyurethane network, b) to change the functionality (increase or decrease), c) to change the polarity by adding polar groups such as ethylene glycol. All these modifications are applicable as long as the non-polar polyester polyol still has a ΔEN <0.38, preferably <0.35, more preferably <0.33. Exemplary non-polar polyester polyols and methods for their preparation can be found in US 2006 / 041156 A1, US 4,742,087 A, US 6,730,768 B2 and M. Ionescu, Chemistry and Technology of polyols for polyurethanes, Rapra 2005, Chapter 17, Polyols from renewable resources - oleochemical polyols. "Non-polar" and "hydrophobic" are used as synonyms in the context of the present invention.
[0022] The functionality of the non-polar polyester polyol (iia) is preferably in the range of 2.0 to 4.0. Preferably, the weight average molecular weight (Mw) of the non-polar polyester polyol (iia) is in the range of 250 g / mol to 2500 g / mol. Preferably, the water absorption of the non-polar polyester polyol (iia) is <0.4 wt. %, more preferably <0.35 wt. %, based on the total weight of the non-polar polyester polyol (iia). Based on the total weight of the polyol composition (ii), the water absorption of the polyol composition (ii) is preferably <0.45 wt. %, more preferably <0.4 wt. %. The values of water absorption are determined in each case according to Reference Example 5. For the polyol composition (ii), a preferred or more preferred water absorption is achieved, for example, by including only non-polar polyester polyol (iia) as polyol (0 wt% to 70 wt% filler content), or if the polyol composition (ii) includes a greater wt% of polyether polyol than the wt% of non-polar polyester polyol (iia), preferably adjusting the filler content to >25 wt%, more preferably to >40 wt%, optionally in combination with dry filling prior to use. For the polyol composition, the water absorption can always be estimated in advance by determining the water absorption of each of the individual components contained in the polyol composition, and adjusting or adjusting, and then mixing the individual components in suitable (weight) amounts, so that the desired water absorption of the polyol composition is achieved or can be achieved. Based on the determination of the water absorption of the individual components and the comparison with each other, suitable individual components can also be selected so that the desired overall low water absorption of the polyol composition is achieved or can be achieved.
[0023] In some embodiments, the present invention relates to a laminate comprising at least one layer of a layered mineral material and a polyurethane layer, wherein the polyurethane of the polyurethane layer is obtained or obtainable from a mixture comprising:
[0024] (i) a polyisocyanate composition;
[0025] (ii) a polyol composition comprising
[0026] (iia) at least one non-polar polyester polyol having an average electronegativity difference ΔEN<0.38, wherein ΔEN is the sum of the electronegativity differences (δEN) of all bonds in the non-polar polyester polyol divided by the total number of bonds in the non-polar polyester polyol, and / or, based on the total weight of the non-polar polyester polyol (iia), the water absorption of the non-polar polyester polyol determined according to Reference Example 5 is <0.4 wt. %, preferably <0.35 wt. %,
[0027] Preferably, based on the total weight of the polyol composition (ii), the polyol composition
[0028] (ii) has a water absorption of <0.45 wt % determined according to Reference Example 5, more preferably
[0029] <0.4 wt%.
[0030] In some embodiments, the present invention relates to a laminate comprising at least one layer of a layered mineral material and a polyurethane layer, wherein the polyurethane of the polyurethane layer is obtained or obtainable from a mixture comprising:
[0031] (i) a polyisocyanate composition;
[0032] (ii) a polyol composition comprising
[0033] (iia) at least one non-polar polyester polyol, preferably, the non-polar polyester polyol has an average electronegativity difference ΔEN<0.38, wherein ΔEN is the sum of the electronegativity differences (δEN) of all bonds in the non-polar polyester polyol divided by the total number of bonds in the non-polar polyester polyol,
[0034] Wherein, based on the total weight of the non-polar polyester polyol (iia), the water absorption of the non-polar polyester polyol (iia) determined according to Reference Example 5 is less than 0.4 wt %, more preferably
[0035] <0.35% by weight
[0036] Preferably, the water absorption of the polyol composition (ii) determined according to Reference Example 5 is <0.45 wt %, more preferably <0.4 wt %, based on the total weight of the polyol composition (ii).
[0037] "Layered mineral materials" are characterized by strong chemical bonds between individual substructures forming two-dimensional layers. The bonding forces within each two-dimensional layer are stronger than the interlayer bonding between different layers. The lateral dimensions of these layers are greater than 1 mm. In contrast to two-dimensional (2D) materials such as graphene, layered mineral materials have layer thicknesses above 1 nm. These layers are oriented approximately parallel to each other, wherein "orientated approximately parallel" means that the two layers may be corrugated or twisted, causing deformations and may form angles in the range of -20° to +20°.
[0038] In some preferred embodiments of the laminate, the hydroxyl value of the polyol composition (ii) is in the range of 150 mg KOH to 500 mg KOH per gram of the sum of all liquid components of the polyol (ii). "Liquid" means that the component is liquid at 25° C. and 1013 mbar, i.e., the viscosity at this temperature and pressure is less than 80,000 mPas, preferably less than 25,000 mPas. In some preferred embodiments of the laminate, the average functionality of the polyol composition (ii) for all polyols contained therein is in the range of 1.8 to 3.5.
[0039] In addition to the non-polar polyester polyol, further isocyanate-reactive compounds can be used as part of the polyol composition (ii), which further isocyanate-reactive compounds are preferably selected from the group of compounds having at least 1.5 isocyanate-reactive groups and compounds having at least 2 isocyanate-reactive groups. Substances containing at least two isocyanate-reactive groups are well known, for example "Plastics Handbook, 7, Polyurethanes", Carl Hanser-Verlag, 3rd edition, 1993, Chapter 3.1). Substances containing at least two isocyanate-reactive groups can be, for example, polyester polyols, polyether polyols, polycarbonate polyols, polybutadiene polyols or polycaprolactone polyols. The preferred functionality of these polyols is 2 to 4, in particular 2 to 3. Preferred polyether polyols contain more than 50% secondary hydroxyl groups, more preferably more than 75% secondary OH groups. Preferred polyester polyols contain more than 50% primary hydroxyl groups.
[0040] As compounds having an average of at least 1.5 isocyanate-reactive groups, it is possible to use all compounds known from polyurethane chemistry which have hydrogen atoms which are reactive toward isocyanates.
[0041] The average functionality of the additional isocyanate-reactive compounds is at least 1.5, preferably in the range of 1.7 to 8, more preferably in the range of 1.9 to 6, and more preferably in the range of 2 to 4. These additional isocyanate-reactive compounds include chain extenders and crosslinkers with an OH functionality in the range of 2 to 6 and a molecular weight of less than 300 g / mol, preferably with a functionality in the range of 2 to 4 and more preferably in the range of 2 to 3, and higher molecular weight compounds having hydrogen atoms reactive toward isocyanates and a number average molecular weight of at least 300 g / mol.
[0042] Molecules with two hydrogen atoms reactive toward isocyanates are referred to as chain extenders, and molecules with more than two hydrogen atoms reactive toward isocyanates are referred to as crosslinkers. Chain extenders and crosslinkers can be used individually or preferably in the form of a mixture. Preferably, diamines, diols and / or triols having a molecular weight of less than 300 g / mol, more preferably in the range of 62 g / mol to less than 300 g / mol, more preferably in the range of 62 g / mol to 250 g / mol are used. For example, aliphatic, alicyclic and / or araliphatic or aromatic diamines and diols containing carbon atoms in the range of 2 to 14, preferably in the range of 2 to 10, can be used. Examples include diethyltoluenediamine (DEDTA), metaphenylenediamine, ethylene glycol, 1,2-propylene glycol, 2-methyl-1,3-propylene glycol, 1,3-propylene glycol, 1,4-butanediol, 1,6-hexanediol, 1,10-decanediol and bis-(2-hydroxyethyl)-hydroquinone (HQEE), 1,2-dihydroxycyclohexane, 1,3-dihydroxycyclohexane, 1,4-dihydroxycyclohexane, bisphenol-A-bis(hydroxyethyl ether), diethylene glycol, dipropylene glycol, tripropylene glycol. Further examples include triols such as 1,2,4-trihydroxycyclohexane, 1,3,5-trihydroxycyclohexane, glycerol and trimethylolpropane; diethanolamine; triethanolamine; and low molecular weight hydroxyl group-containing polyalkylene oxides based on ethylene oxide and / or 1,2-propylene oxide; as well as the above diols and / or triols as starting molecules. Particularly preferred crosslinking agents are low molecular weight, hydroxyl group-containing polyalkylene oxides based on ethylene oxide and / or 1,2-propylene oxide, more preferably based on 1,2-propylene oxide, and trifunctional starters, preferably glycerol and trimethylolpropane. Particularly preferred chain extenders are selected from the group consisting of ethylene glycol, 1,2-propylene glycol, 1,3-propylene glycol, 2-methyl-1,3-propanediol, 1,4-butanediol, diethylene glycol, bis-(2-hydroxyethyl)-hydroquinone, dipropylene glycol and mixtures of two or more thereof.
[0043] If chain extenders and / or crosslinkers are used, the proportion of chain extenders and / or crosslinkers is preferably in the range of 1% to 50% by weight, more preferably in the range of 2% to 20% by weight, based on the total weight of the polyol composition (ii). However, it is also possible to operate without chain extenders and / or crosslinkers. However, in order to modify the mechanical properties, such as hardness, it may prove advantageous to add chain extenders, crosslinkers or mixtures thereof, if desired.
[0044] The number average molecular weight of the higher molecular weight compound having hydrogen atoms reactive to isocyanate is preferably 400 g / mol to 15000 g / mol. For example, a compound selected from the group consisting of polyether polyols, polyester polyols, polytetrahydrofuran polyols, polybutadiene polyols, polycaprolactone polyols, polycarbonate polyols or mixtures thereof can be used.
[0045] Polyether polyols are produced, for example, from epoxides such as propylene oxide and / or ethylene oxide, or from tetrahydrofuran with hydrogen-active starter compounds such as aliphatic alcohols, phenols, amines, carboxylic acids, water or compounds based on natural substances such as sucrose, sorbitol or mannitol using catalysts. Basic catalysts or double metal cyanide catalysts may be mentioned here.
[0046] Polyester polyols are prepared, for example, from aliphatic or aromatic dicarboxylic acids and polyols, polythioether polyols, polyesteramides, polyacetals containing hydroxyl groups and / or aliphatic polycarbonates containing hydroxyl groups, preferably in the presence of an esterification catalyst. Other possible polyols are, for example, "Plastics Handbook, 7, Polyurethanes", Carl Hanser-Verlag, 3rd edition, 1993, Chapter 3.1.
[0047] The polyol composition (ii) may contain a catalyst.
[0048] Common polyurethane catalysts can be used as catalysts. These catalysts greatly accelerate the reaction of compounds (b) having hydrogen atoms reactive toward isocyanates with diisocyanates and polyisocyanates (a). Common catalysts that can be used to prepare polyurethanes are, for example: amidines such as 2,3-dimethyl-3,4,5,6-tetrahydropyrimidine, tertiary amines such as triethylamine, tributylamine, dimethylbenzylamine, dimethylcyclohexylamine, N-methyl-morpholine, N-ethyl-morpholine, N-cyclohexylmorpholine, N,N,N',N'-tetramethylethylenediamine, N,N,N',N'-tetramethyl-butylenediamine, N,N,N',N'-tetramethyl-hexanediamine, Pentamethyl-diethylenetriamine, tetramethyl-diaminoethyl ether, bis-(dimethylaminopropyl)-urea, dimethylpiperazine, 1,2-dimethylimidazole, 1-aza-bicyclo-(3,3,0)-octane and preferably 1,4-diaza-bicyclo-(2,2,2)-octane, and alkanolamine compounds such as triethanolamine, triisopropanolamine, N-methyl-diethanolamine and N-ethyl-diethanolamine and dimethylethanolamine. Also contemplated are organometallic compounds, preferably organotin compounds, such as tin(II) salts of organic carboxylic acids, for example tin(II) acetate, tin(II) octoate, tin(II) ethylhexanoate and tin(II) laurate, and dialkyltin(IV) salts of organic carboxylic acids, for example dibutyltin(IV), for example dibutyltin diacetate, dibutyltin dilaurate, dibutyltin maleate and dioctyltin diacetate; and bismuth carboxylates, such as bismuth(III) neodecanoate, bismuth 2-ethylhexanoate and bismuth octoate or mixtures thereof. The organometallic compounds can be used alone or preferably in combination with strongly basic amines. If component (b) is an ester, preferably only amine catalysts are used.
[0049] Catalyst (d) may be used as catalyst or catalyst combination in a concentration of, for example, 0.001 to 5% by weight, specifically 0.05 to 2% by weight, based on the total weight of the polyol composition (ii).
[0050] In addition, additives can be used in the polyol component (ii). All known auxiliary agents and additives for the production of polyurethanes can be used. Examples include surfactants, foam stabilizers, cell regulators, release agents, plasticizers, fillers, dyes, pigments, flame retardants, hydrolysis inhibitors, fungistatic and antibacterial substances. Such substances are known and used in, for example, "Plastics Handbook, 7, Polyurethanes", Carl Hanser-Verlag, 3rd edition, 1993, Chapter 3.4.4 and Chapter 3.4.6 to Chapter 3.4.11. Preferred additives are organophosphorus compounds and / or organohalogen compounds. In some preferred embodiments, auxiliary agents and additives may include alkaline catalysts other than conventional catalysts for forming polyurethanes. For example, these include catalysts for forming polyisocyanurates. Polyisocyanurate catalysts include alkali metal carboxylates. These preferably include formates and acetates, particularly acetates such as sodium acetate and potassium acetate.
[0051] Preferably, in the preparation of the polyurethane layer according to the invention, the polyisocyanate of the polyisocyanate composition (i), the compound containing hydrogen atoms reactive toward isocyanate groups and, if used, the further compound containing hydrogen atoms reactive toward isocyanate groups are reacted in such an amount that the equivalent ratio of NCO groups of the polyisocyanate of the polyisocyanate composition (i) to the sum of the hydrogen atoms of the further components reactive toward isocyanate groups is in the range of 0.7 to 1.4, preferably in the range of 0.8 to 1.2, more preferably in the range of 0.9 to 1.1 and more preferably in the range of 1.0. A ratio of 1:1 corresponds to an isocyanate index of 100.
[0052] The term "polyurethane" in the context of the present invention includes all known polyisocyanate polyaddition products. These include addition products of isocyanates and alcohols and modified polyurethanes, which may contain isocyanurates, allophanates, ureas, carbodiimides, uretonimines, biuret structures and other isocyanate addition products.
[0053] In some preferred embodiments of the laminate, the laminate comprises fibers embedded in a polyurethane layer. The polyurethane is cured in the presence of the fibers. "Embedded in the polyurethane layer" means that no part of the fibers is free and uncoated on the surface of the laminate, wherein the minimum layer thickness of the polyurethane layer between the embedded fibers and the surface is still ≥ 0.1 μm.
[0054] In some preferred embodiments of the laminate, the fibers are textiles or chopped fibers, wherein the textiles include woven textiles or nonwoven textiles or knitted textiles or non-wrinkled textiles and combinations of two or more thereof, wherein the area weight of the textile is preferably <300 g / m 2 , more preferably <200g / m 2 , more preferably at 20g / m 2 Up to 175g / m 2 In the range of 30 g / m 2 Up to 150g / m 2 The average length of the chopped fibers is in the range of 1 mm to 10 mm, preferably 2 mm to 6 mm and the diameter is 10 μm to 15 μm. The preferred fibers are glass fibers.
[0055] The material of the textile preferably comprises a material selected from the group consisting of glass, carbon, polyester, aramid, polyethylene, polypropylene, polyamide, polyester-polyarylate, poly(p-phenylene-2,6-benzobisoxazole), basalt, asbestos, boron, silicon carbide, metal, natural materials (such as hemp, flax, jute, kenaf, coconut, bamboo, straw, cotton, silk, wool, collagen, keratin, chitin, chitosan) and mixtures thereof. All textile weaving patterns known to those skilled in the art can be considered. High air permeability of the textile and rapid wetting with resin are preferred. The material of the chopped fibers includes a material selected from the group consisting of carbon, polyester, aromatic polyamide, polyethylene, polypropylene, polyamide, polyester-polyarylate, poly(p-phenylene-2,6-benzobisoxazole), basalt, asbestos, boron, silicon carbide, hemp, flax, jute, kenaf, coconut, bamboo, straw, cotton and mixtures thereof and mixtures of two or more thereof. Preferably, the chopped fibers are glass fibers having an average length in the range of 1 mm to 10 mm, preferably 2 mm to 6 mm and a diameter of 10 μm to 15 μm.
[0056] In some preferred embodiments of the laminate, the mixture comprising components (i) and (ii) comprises >7% bio-based carbon determined according to ASTM D6866-21, relative to 100% total carbon in the mixture; preferably in the range of 7.5% to 60%, more preferably in the range of 8.5% to 50%, determined according to ASTM D6866-21, relative to 100% total carbon in the mixture, preferably determined according to Reference Example 4.
[0057] In some preferred embodiments of the laminate, the mixture further comprises
[0058] (iib) Dispersions comprising solid fillers and preferably polyether polyols and / or additionally polyester polyols.
[0059] In some preferred embodiments, the mixture consists of (i), (iia) and (iib). In some embodiments, the mixture comprises at least one non-polar polyester polyol (from (iia)), optionally additional polyester polyols (from (iib)) and polyether polyols (from (iib)).
[0060] In some preferred embodiments of the laminate, the filler is selected from the group consisting of TiO2, carbon black, graphite, zeolite, and mixtures of two or more of these fillers.
[0061] In some preferred embodiments of the laminate, the filler is selected from the group consisting of melamine, melamine cyanurate, expandable graphite, ammonium polyphosphate, aluminum oxide, aluminum hydroxide, magnesium hydroxide, and a mixture of two or more thereof.
[0062] In some preferred embodiments of the laminate, the dispersion (iib) is prepared by grinding the filler in the polyol with a ball mill in the presence of a dispersing additive. The particle size distribution shows a d90 value of less than 50 μm according to ISO 13320:01 2020. In some embodiments, the d90 value of the particle size distribution is <4 μm.
[0063] In some preferred embodiments of the laminate, the isocyanate composition according to (i) comprises a polyisocyanate, preferably a diisocyanate, more preferably a (di)isocyanate obtained or obtainable from a diisocyanate and a polyether polyol. In another preferred embodiment, the isocyanate comprises a polyisocyanate.
[0064] The polyisocyanate composition (i) comprises at least one polyisocyanate (ia). At least one polyisocyanate (ia) is an organic compound containing at least two reactive isocyanate groups per molecule, i.e., a functionality of at least 2. The polyisocyanate composition (i) comprises one polyisocyanate or a mixture of two or more polyisocyanates. If the polyisocyanate or mixture used does not have a uniform functionality, the number-weighted average of the functionality of at least one polyisocyanate (ia) is at least 2. The average functionality of suitable diisocyanates and polyisocyanates is in the range of 2.0 to 2.9, preferably in the range of 2.1 to 2.8. The viscosity at 23° C. according to DIN 53019-1 to 3 is in the range of 5 mPas to 1000 mPas, preferably in the range of 10 mPas to 600 mPas. At least one polyisocyanate (ia) is selected from the group consisting of aliphatic, alicyclic, aromatic aliphatic polyisocyanates and mixtures thereof, preferably at least one polyisocyanate (ia) comprises at least one aromatic polyisocyanate. Such polyisocyanates are known per se or can be prepared by methods known per se. As mentioned above, polyisocyanates can also be used as mixtures in particular, so that in this case at least one polyisocyanate (ia) contains different polyisocyanates. Preferably, at least one polyisocyanate (ia) has two (hereinafter referred to as diisocyanates) or more than two isocyanate groups per molecule.Preferably, the at least one polyisocyanate (ia) is selected from the group consisting of alkylene diisocyanates having 4 to 12 carbon atoms in the alkylene radical, in particular 1,12-dodecane diisocyanate, 2-ethyltetramethylene-1,4-diisocyanate, 2-methylpentamethylene-1,5-diisocyanate, tetramethylene-1,4-diisocyanate and preferably hexamethylene-1,6-diisocyanate; cycloaliphatic diisocyanates, in particular cyclohexane-1,3-diisocyanate and cyclohexane-1,4-diisocyanate and any mixtures of these isomers, 1-isocyanato-3,3,5-trimethyl-5-isocyanatomethylcyclohexane (IPDI), hexahydrotoluene-2,4-diisocyanate and hexahydrotoluene-2,6-diisocyanate and the corresponding isomer mixtures, dicyclohexylmethane-4,4'-diisocyanate, dicyclohexylmethane -2,2'-diisocyanate and dicyclohexylmethane-2,4'-diisocyanate and the corresponding isomer mixtures; and aromatic polyisocyanates, in particular toluene-2,4-diisocyanate and toluene-2,6-diisocyanate and the corresponding isomer mixtures, diphenylmethane-4,4'-diisocyanate, diphenylmethane-2,4'-diisocyanate and diphenylmethane-2,2'-diisocyanate and the corresponding isomer mixtures, a mixture of diphenylmethane-4,4'-diisocyanate and diphenylmethane-2,2'-diisocyanate, polyphenylpolymethylene polyisocyanate, a mixture of diphenylmethane-4,4'-diisocyanate, diphenylmethane-2,4'-diisocyanate and diphenylmethane-2,2'-diisocyanate, and polyphenylpolymethylene polyisocyanate (crude MDI), and a mixture of crude MDI and toluene diisocyanate.Further preferably, the at least one polyisocyanate (ia) is selected from the group consisting of diphenylmethane-2,2'-diisocyanate, diphenylmethane-2,4'-diisocyanate and / or diphenylmethane-4,4'-diisocyanate (MDI), polymeric diphenylmethane diisocyanate (pMDI), naphthylene-1,5-diisocyanate (NDI), toluene-2,4-diisocyanate and / or toluene-2,6-diisocyanate (TDI), dimethyl diphenyl-3,3'-diisocyanate, diphenylethane-1,2-diisocyanate and / or p-phenylene diisocyanate (PPDI), trimethylene diisocyanate, tetramethylene diisocyanate, pentamethylene diisocyanate, hexamethylene diisocyanate, heptamethylene diisocyanate and / or octamethylene diisocyanate. cyanate, 2-methylpentamethylene-1,5-diisocyanate, 2-ethylbutylene-1,4-diisocyanate, pentamethylene-1,5-diisocyanate, butylene-1,4-diisocyanate, 1-isocyanato-3,3,5-trimethyl-5-isocyanatomethyl-cyclohexane (isophorone diisocyanate, IPDI), 1,4-bis(isocyanatomethyl)cyclohexane and / or 1,3-bis(isocyanatomethyl)cyclohexane The invention relates to polyisocyanates of the present invention. The polyisocyanates of the present invention are cyclohexane (HXDI), cyclohexane-1,4-diisocyanate, 1-methyl-cyclohexane-2,4-diisocyanate and / or 1-methyl-cyclohexane-2,6-diisocyanate and dicyclohexylmethane 4,4'-diisocyanate, dicyclohexylmethane 2,4'-diisocyanate and / or dicyclohexylmethane-2,2'-diisocyanate, and mixtures of two or more of these polyisocyanates. Modified polyisocyanates are also often used, i.e., products obtained by chemical reactions of organic polyisocyanates having at least two reactive isocyanate groups per molecule. Particular mention is made of polyisocyanates containing esters, ureas, biuret, allophanates, carbodiimides, isocyanurates, uretdiones, carbamates and / or urethane groups. At least one polyisocyanate (ia) can be used in whole or in part in the form of polyisocyanate prepolymers. These polyisocyanate prepolymers can be obtained by reacting the polyisocyanates of the above-mentioned at least one polyisocyanate (ia) in advance in whole or in part with a polymeric compound reactive to isocyanate to form an isocyanate prepolymer. The reaction is carried out under an excess of at least one polyisocyanate (ia), for example in the range of 30° C. to 100° C., preferably at a temperature of about 80° C. Suitable polymeric compounds having groups reactive to isocyanate are known to those skilled in the art and are described, for example, in “Plastics Handbook, 7, Polyurethanes”, Carl Hanser-Verlag, 3rd edition, 1993, chapter 3.1.In principle, all known compounds having at least two isocyanate-reactive hydrogen atoms can be considered as polymeric compounds having isocyanate-reactive groups, for example those having a functionality in the range of 2 to 8 and a number average molecular weight Mn in the range of 400 g / mol to 15000 g / mol. For example, compounds selected from the group of polyether polyols, polyester polyols, polycarbonate polyols, polybutadiene polyols, polycaprolactone polyols, polyisocyanates and polyisocyanurates can be used. Preferred prepolymers have an NCO content in the range of 10% to 50% by weight, preferably in the range of 15% to 32% by weight.
[0065] In a preferred embodiment, the mixture obtained or obtainable polyurethane does not contain solvent substantially. In particular, components (i) and (ii) do not contain solvent substantially. "Substantially solvent-free" should be understood to mean that except for possible impurities based on manufacturing, they do not contain solvent and do not add solvent to these components. Therefore, based on the gross weight of the mixture of 100 wt % is also the gross weight of components (i) and (ii), the solvent content is lower than 1 wt %, preferably lower than 0.1 wt %, and more preferably lower than 0.01 wt %. In contrast, based on the gross weight of its polyol composition of 100 wt %, as used in EP 3 785 900 A1, according to the safety data sheet, the polyol composition of " PU NEUKADUR PN 9712 2-C polyurethane adhesive " has a solvent content of 3.8 wt %.
[0066] The term "solvent" is common knowledge in the relevant art. Solvents for the purposes of the present invention should be understood in the broadest sense to include organic and inorganic liquids that can physically dissolve other solid substances. A prerequisite for a material to be used as a solvent is that neither the dissolved material nor the dissolved material undergoes chemical changes during the dissolution process. Therefore, the dissolved components can be recovered by physical separation methods (such as distillation, crystallization, sublimation, evaporation and / or adsorption).
[0067] In the context of the present invention, the mixture is substantially free of organic solvents. In some preferred embodiments of the laminate, the mixture of (i) and (ii) comprises less than 0.1 wt. %, more preferably less than 0.01 wt. % of components (i) and (ii), based on the total weight of the mixture being 100 wt. %, which is also the total weight of components (i) and (ii). More specifically, the polyurethane system components substantially do not contain ethers or glycol ethers (such as diethyl ether, dibutyl ether, anisole, dioxane, monomeric tetrahydrofuran), ketones (such as acetone, butanone, cyclohexanone), esters (such as ethyl acetate, esters of acrylic acid or methacrylic acid), nitrogen compounds (such as dimethylformamide, pyridine, N-methylpyrrolidone, acetonitrile), sulfur compounds (such as carbon disulfide, dimethyl sulfoxide, cyclopentane), nitro compounds (such as nitrobenzene), (hydro)halogenated carbons (such as dichloromethane, chloroform, tetrachloromethane, trichloroethylene, tetrachloroethylene, 1,2-dichloroethane, chlorofluorocarbons), hydrocarbons (preferably hydrocarbons having a boiling point above 60° C., such as octane, methylcyclohexane, decalin, benzene, toluene, styrene, xylene).
[0068] In some preferred embodiments of the laminate, the at least one non-polar polyester polyol (iia) contains polyether units in the range of zero wt% to 25 wt%, based on the total weight of the at least one non-polar polyester polyol (iia). In some preferred embodiments of the laminate, the content of polyester polyol units is > 20 wt%, based on the total weight of all liquid components present in (i) and (ii).
[0069] In some preferred embodiments of the laminate, the at least one non-polar polyester polyol (iia) comprises polyester polyol units and optionally polyether units, based on the total weight of all liquid components present in (i) and (ii), wherein the content of polyester polyol units is in the range of 55 to 100% by weight, preferably in the range of 65 to 100% by weight, more preferably in the range of 75 to 100% by weight. The expression "liquid components" present in (i) and (ii) refers to all components of (i) and (ii) which are liquid at 25°C and 1013 mbar, i.e. they have a viscosity of less than 80000 mPas at this temperature and pressure. The at least one non-polar polyester polyol (iia) is liquid at 25°C and 1013 mbar. In the case where the at least one non-polar polyester polyol (iia) does not contain polyether units, the content of polyester polyol units is 100% by weight, i.e. the same as the total weight of the at least one non-polar polyester polyol (iia). In the case of the presence of polyether units, the content of polyester polyol units and polyether units in the at least one non-polar polyester polyol (iia) is determined by taking the molecular weight of the at least one non-polar polyester polyol (iia) as the basis. The content of polyether units is then determined, wherein for each polyether unit, which is derived from a polyol X comprising at least two hydroxyl groups and at least one ether bridge and reacted with a polyester polyol Y, wherein the ether bridge is formed by a hydroxyl group of the polyol and a suitable functional group of the polyester (e.g. an epoxy group of the polyester polyol), the molecular weight of the remainder X' of the polyol X in the at least one non-polar polyester polyol (iia) is determined, which corresponds to the molecular weight of the polyol X before the reaction minus the molecular weight of the hydrogen atoms of the hydroxyl groups forming the ether bridge. In addition, for example, if the alcohol component contains ether groups, the ether bridge is formed by an ester exchange reaction. The molecular weight of the remainder X' is then set relative to the total weight of the at least one polyester polyol (iia) as 100% by weight. For the polyester unit, the molecular weight of the remaining part Y' of the polyester polyol Y in the polyester polyol (iia) is determined, and then the molecular weight of the remaining part Y' is set relative to the total weight of the at least one non-polar polyester polyol (iia) as 100 wt%. "At least one non-polar polyester polyol (iia)" means that the polyester polyol (iia) contains one or two or more non-polar polyester polyols.
[0070] In some preferred embodiments of the laminate, the polyisocyanate composition (i) and / or the polyol composition (ii) comprises one or more liquid and / or solid flame retardants.
[0071] In some preferred embodiments of the laminate, the polyol composition (ii) comprises at least 1 ppm iron (in the form of iron cations).
[0072] In some preferred embodiments of the laminate, the layered mineral material is preferably a layered natural stone, more preferably selected from the group consisting of slate, mica, graphite, glimmer, layered silicates (e.g., calcite, kaolin, talc), montmorillonite, molybdenum (IV) sulfate, and mixtures of two or more of these layered mineral materials, wherein the layered mineral material preferably comprises at least slate, more preferably consists of slate. The layered mineral material preferably comprises at least slate, more preferably consists of slate, which means that the layered mineral material comprises or consists of slate, wherein the slate itself may contain impurities, such as enclosed quartz or additional materials or minerals.
[0073] In some preferred embodiments of the laminate, the layered mineral material is cut parallel to its layered structure, and wherein the roughness R of the mineral surface intended for producing the laminate is a (arithmetic mean height according to ISO 25178, measured by laser scanning microscope Keyence VK-X3000 according to DIN EN ISO 4287:2010-07) greater than 1.5 μm, in particular greater than 2 μm. The water content of the layered mineral material is preferably <25% by weight, based on 100% by weight of the total weight of the layered mineral material.
[0074] In some preferred embodiments, the area weight of the laminate is 500 g / m 2 Up to 1800g / m 2 In the range of 900 g / m 2 Up to 1500g / m 2 within the range.
[0075] In some preferred embodiments, the thickness of the laminate is less than 2 mm, preferably less than 1.5 mm, more preferably in the range of 0.5 mm to 1.0 mm, more preferably in the range of 0.7 mm to 0.9 mm. In some alternative preferred embodiments, the thickness of the laminate is less than 0.3 mm, preferably in the range of 0.1 mm to 0.3 mm. Laminates with a thickness of less than 0.3 mm, preferably in the range of 0.1 mm to 0.3 mm, are preferably made with a small amount of filler, which means less than 4 wt% filler, based on the total weight of the mixture being 100 wt%. Laminates with a thickness of less than 0.3 mm are bendable based on gravity alone and are not rigid materials, such as oilcloth.
[0076] Aspect 2 - Method for preparing a laminate
[0077] According to a second aspect, the present invention relates to a method for preparing a laminate, preferably a laminate according to the first aspect as described above, wherein the laminate comprises layers of a layered mineral material and at least one polyurethane layer, the method comprising:
[0078] (a) providing components for a mixture, the mixture comprising at least:
[0079] (i) a polyisocyanate composition;
[0080] (ii) a polyol composition comprising at least one non-polar polyester polyol (iia), wherein the average electronegativity difference ΔEN of the non-polar polyester polyol is less than 0.38, wherein ΔEN is the electronegativity difference of all bonds in the non-polar polyester polyol
[0081] The sum of (δEN) divided by the total number of bonds in the non-polar polyester polyol,
[0082] and mixing (i) and (ii) to form a mixture;
[0083] (b) providing a three-dimensional body of layered mineral material;
[0084] (c) applying a first layer of the mixture according to (a) onto a surface of a three-dimensional body of layered mineral material, wherein the surface is oriented approximately parallel to the layers of the layered mineral material, thereby forming a layer of the mixture on the surface;
[0085] (d) applying a second layer of the mixture according to (a) on top of the first layer;
[0086] (e) optionally applying a third layer of the mixture according to (a) on top of the second layer, thereby forming an at least partially uncured laminate;
[0087] (f) optionally curing the laminate obtained in (e) at a temperature above room temperature.
[0088] The mixture according to (a) is preferably applied in steps (d) and (e) as long as the polyurethane system components (ie the mixture obtained in (b)) have not yet completely cured, ie as long as the reaction of isocyanate groups with OH groups is still taking place.
[0089] In some embodiments, the present invention relates to a method for preparing a laminate, wherein the laminate comprises a layer of a layered mineral material and at least one polyurethane layer, the method comprising:
[0090] (a) providing components for a mixture, the mixture comprising at least:
[0091] (i) a polyisocyanate composition;
[0092] (ii) a polyol composition comprising at least one non-polar polyester polyol (iia), wherein the average electronegativity difference ΔEN of the non-polar polyester polyol is less than 0.38, wherein ΔEN is the electronegativity difference of all bonds in the non-polar polyester polyol
[0093] The sum of (δEN) divided by the total number of bonds in the non-polar polyester polyol and / or the water absorption of the non-polar polyester polyol determined according to Reference Example 5 is <0.4 wt. %, preferably <0.35 wt. %, based on the total weight of the non-polar polyester polyol (iia),
[0094] Preferably, based on the total weight of the polyol composition (ii), the water absorption of the polyol composition (ii) determined according to Reference Example 5 is <0.45 wt %, more preferably <0.4 wt %,
[0095] and mixing (i) and (ii) to form a mixture;
[0096] (b) providing a three-dimensional body of layered mineral material;
[0097] (c) applying a first layer of the mixture according to (a) onto a surface of a three-dimensional body of layered mineral material, wherein the surface is oriented approximately parallel to the layers of the layered mineral material, thereby forming a layer of the mixture on the surface;
[0098] (d) applying a second layer of the mixture according to (a) on top of the first layer;
[0099] (e) optionally applying a third layer of the mixture according to (a) on top of the second layer, thereby forming an at least partially uncured laminate;
[0100] (f) optionally curing the laminate obtained in (e) at a temperature above room temperature.
[0101] In some embodiments, the present invention relates to a method for preparing a laminate, wherein the laminate comprises a layer of a layered mineral material and at least one polyurethane layer, the method comprising:
[0102] (a) providing components for a mixture, the mixture comprising at least:
[0103] (i) a polyisocyanate composition;
[0104] (ii) a polyol composition comprising at least one non-polar polyester polyol (iia), preferably, the non-polar polyester polyol has an average electronegativity difference ΔEN<0.38, wherein ΔEN is the sum of the electronegativity differences (δEN) of all bonds in the non-polar polyester polyol divided by the total number of bonds in the non-polar polyester polyol, wherein the water absorption of the non-polar polyester polyol (iia) determined according to Reference Example 5 is <0.4 wt %, based on the total weight of the non-polar polyester polyol (iia), more preferably
[0105] <0.35% by weight
[0106] Preferably, based on the total weight of the polyol composition (ii), the water absorption of the polyol composition (ii) determined according to Reference Example 5 is <0.45 wt %, more preferably <0.4 wt %;
[0107] and mixing (i) and (ii) to form a mixture;
[0108] (b) providing a three-dimensional body of layered mineral material;
[0109] (c) applying a first layer of the mixture according to (a) onto a surface of a three-dimensional body of layered mineral material, wherein the surface is oriented approximately parallel to the layers of the layered mineral material, thereby forming a layer of the mixture on the surface;
[0110] (d) applying a second layer of the mixture according to (a) on top of the first layer;
[0111] (e) optionally applying a third layer of the mixture according to (a) on top of the second layer, thereby forming an at least partially uncured laminate;
[0112] (f) optionally curing the laminate obtained in (e) at a temperature above room temperature.
[0113] The surface of the three-dimensional body being oriented approximately parallel to the layers of the layered mineral material means that the surface can be arranged at an angle in the range of -20° to +20° relative to at least the first layer of the layered mineral material. Room temperature preferably means 23° C. The maximum humidity of the three-dimensional body of the layered mineral material provided according to (b) is preferably 25% by weight: preferably at least (c) to (f), more preferably (a) to (f), is carried out at a humidity of the surrounding atmosphere (preferably air) of at most 45% by weight.
[0114] Aspect 3 - Method for preparing a laminate
[0115] According to a third aspect, the present invention relates to an alternative method for preparing a laminate, preferably a laminate of the first aspect as described above, wherein the laminate comprises layers of a layered mineral material and at least one polyurethane layer, the method comprising:
[0116] (a) providing components for forming a mixture, the mixture comprising at least:
[0117] (i) a polyisocyanate composition;
[0118] (ii) a polyol composition comprising at least one non-polar polyester polyol (iia), wherein the average electronegativity difference ΔEN of the non-polar polyester polyol is less than 0.38, wherein ΔEN is the electronegativity difference of all bonds in the non-polar polyester polyol
[0119] The sum of (δEN) divided by the total number of bonds in the non-polar polyester polyol,
[0120] and mixing (i) and (ii) to form a mixture;
[0121] (b) providing a three-dimensional body of layered mineral material;
[0122] (c) applying a first layer of the mixture according to (a) onto a surface of a three-dimensional body of layered mineral material, wherein the surface is oriented approximately parallel to the layers of the layered mineral material, thereby forming a layer of the mixture on the surface;
[0123] (d) reacting (i) and (ii) of the mixture, thereby forming a polyurethane layer on the surface of the three-dimensional body of the layered mineral material, the polyurethane layer being at least partially connected to at least the first layer of the layered mineral material;
[0124] (e) applying a second layer of the mixture according to (a) on top of the polyurethane layer formed in (d),
[0125] (f) applying a textile layer on top of the second layer and applying a force to embed the textile layer, wherein the applied force is preferably 2.5 N / mm 2 Up to 30N / mm 2 within the scope of
[0126] (g) optionally applying a third or more layers of the mixture according to (a) on top of the embedded textile layer of (f); thereby forming an at least partially uncured laminate;
[0127] (h) optionally curing the laminate at a temperature above room temperature.
[0128] In some embodiments, the present invention relates to a method for preparing a laminate, wherein the laminate comprises a layer of a layered mineral material and at least one polyurethane layer, the method comprising:
[0129] (a) providing components for forming a mixture, the mixture comprising at least:
[0130] (i) a polyisocyanate composition;
[0131] (ii) a polyol composition comprising at least one non-polar polyester polyol (iia), wherein the average electronegativity difference ΔEN of the non-polar polyester polyol is less than 0.38, wherein ΔEN is the electronegativity difference of all bonds in the non-polar polyester polyol
[0132] The sum of (δEN) divided by the total number of bonds in the non-polar polyester polyol,
[0133] and / or based on the total weight of the non-polar polyester polyol (iia), the water absorption of the non-polar polyester polyol determined according to Reference Example 5 is less than 0.4 wt %, preferably
[0134] <0.35% by weight
[0135] Preferably, based on the total weight of the polyol composition (ii), the water absorption of the polyol composition (ii) determined according to Reference Example 5 is <0.45 wt %, more preferably <0.4 wt %,
[0136] and mixing (i) and (ii) to form a mixture;
[0137] (b) providing a three-dimensional body of layered mineral material;
[0138] (c) applying a first layer of the mixture according to (a) onto a surface of a three-dimensional body of layered mineral material, wherein the surface is oriented approximately parallel to the layers of the layered mineral material, thereby forming a layer of the mixture on the surface;
[0139] (d) reacting (i) and (ii) of the mixture, thereby forming a polyurethane layer on the surface of the three-dimensional body of the layered mineral material, the polyurethane layer being at least partially connected to at least the first layer of the layered mineral material;
[0140] (e) applying a second layer of the mixture according to (a) on top of the polyurethane layer formed in (d),
[0141] (f) applying a textile layer on top of the second layer and applying a force to embed the textile layer, wherein the applied force is preferably 2.5 N / mm 2 Up to 30N / mm 2 within the scope of
[0142] (g) optionally applying a third or more layers of the mixture according to (a) on top of the embedded textile layer of (f); thereby forming an at least partially uncured laminate;
[0143] (h) optionally curing the laminate at a temperature above room temperature.
[0144] In some embodiments, the present invention relates to a method for preparing a laminate, wherein the laminate comprises a layer of a layered mineral material and at least one polyurethane layer, the method comprising:
[0145] (a) providing components for forming a mixture, the mixture comprising at least:
[0146] (i) a polyisocyanate composition;
[0147] (ii) a polyol composition comprising at least one non-polar polyester polyol (iia), preferably, the non-polar polyester polyol has an average electronegativity difference ΔEN<0.38, wherein ΔEN is the sum of the electronegativity differences (δEN) of all bonds in the non-polar polyester polyol divided by the total number of bonds in the non-polar polyester polyol, wherein the water absorption of the non-polar polyester polyol (iia) determined according to Reference Example 5 is <0.4 wt %, based on the total weight of the non-polar polyester polyol (iia), more preferably
[0148] <0.35% by weight
[0149] Preferably, based on the total weight of the polyol composition (ii), the water absorption of the polyol composition (ii) determined according to Reference Example 5 is <0.45 wt %, more preferably <0.4 wt %,
[0150] and mixing (i) and (ii) to form a mixture;
[0151] (b) providing a three-dimensional body of layered mineral material;
[0152] (c) applying a first layer of the mixture according to (a) onto a surface of a three-dimensional body of layered mineral material, wherein the surface is oriented approximately parallel to the layers of the layered mineral material, thereby forming a layer of the mixture on the surface;
[0153] (d) reacting (i) and (ii) of the mixture, thereby forming a polyurethane layer on the surface of the three-dimensional body of the layered mineral material, the polyurethane layer being at least partially connected to at least the first layer of the layered mineral material;
[0154] (e) applying a second layer of the mixture according to (a) on top of the polyurethane layer formed in (d),
[0155] (f) applying a textile layer on top of the second layer and applying a force to embed the textile layer, wherein the applied force is preferably 2.5 N / mm 2 Up to 30N / mm 2 within the scope of
[0156] (g) optionally applying a third or more layers of the mixture according to (a) on top of the embedded textile layer of (f); thereby forming an at least partially uncured laminate;
[0157] (h) optionally curing the laminate at a temperature above room temperature.
[0158] With regard to applying the mixture of (i) and (ii) to the surface of a three-dimensional body of layered mineral material, the following options are used:
[0159] - applying the mixture of (i) and (ii) to the surface of a three-dimensional body of a layered mineral material in the form of multiple layers. The chemical composition of all layers is the same.
[0160] - applying the mixture of (i) and (ii) to the surface of a three-dimensional body of a layered mineral material in the form of multiple layers. The chemical composition of the first layer differs from the composition of the next layer or layers.
[0161] - Applying the mixture of (i) and (ii) to the surface of a three-dimensional body of a layered mineral material in the form of multiple layers. The first layer contains no filler. The subsequent layer or layers contain fillers.
[0162] Preferred embodiments of the method according to the second aspect and the method according to the third aspect
[0163] In some preferred embodiments of the method according to the second aspect or the third aspect, the method comprises:
[0164] (i) Removing the solidified laminate formed in (f) of Embodiment 20 or (h) of Embodiment 21 from the three-dimensional body of layered mineral material, followed by also removing at least the first layer of the layered mineral material, thereby obtaining a (separated) laminate.
[0165] In some preferred embodiments of the method according to the second aspect or the third aspect, (c) comprises:
[0166] (c.1) applying a first portion of the mixture according to (a) onto a surface of a three-dimensional body of layered mineral material, wherein the surface is oriented substantially parallel to the layers of the layered mineral material, thereby forming a first layer of the mixture on the surface;
[0167] (c.2) optionally at least partially reacting (i) and (ii) of the first part of the mixture, thereby forming a first polyurethane layer on the surface of the three-dimensional body of the layered mineral material, the first polyurethane layer being at least partially connected to at least the first layer of the layered mineral material;
[0168] (c.3) applying a second part of the mixture according to (a) onto the first polyurethane layer formed in (c.2), thereby forming a second layer of the mixture on the first polyurethane layer;
[0169] wherein the second part and / or the first part of the mixture according to (a) comprises fibers, or wherein in (c.1) and / or (c.3) the fibers are simultaneously applied to the surface of the three-dimensional body of the layered mineral material;
[0170] Wherein (d) comprises reacting (i) and (ii) of the first and second parts of the mixture, thereby forming a polyurethane layer on the surface of the three-dimensional body of layered mineral material, the polyurethane layer being at least partially connected to at least the first layer of layered mineral material.
[0171] Suitable fibers are selected from the group consisting of glass fibers, carbon fibers, polyester fibers, aramid fibers, polyethylene fibers, polypropylene fibers, polyamide fibers, polyester-polyarylate fibers, poly(p-phenylene-2,6-benzobisoxazole) fibers, basalt fibers, asbestos fibers, boron fibers, silicon carbide fibers, metal fibers, natural fibers (such as hemp, flax, jute, kenaf, coconut, bamboo, straw, cotton, silk, wool, collagen, keratin, chitin, chitosan) and mixtures of two or more of these fibers. Preferably, the fibers are chopped fibers and have an average length in the range of 1 mm to 10 mm, preferably in the range of 2 mm to 6 mm, and a diameter of 10 μm to 15 μm. More preferably, the fibers are chopped glass fibers, having an average length in the range of 1 mm to 10 mm, preferably in the range of 2 mm to 6 mm, and a diameter of 10 μm to 15 μm. The expression "the first part and the second part of the mixture according to (a) comprise fibers" means that the first part of the mixture according to (a) comprises fibers and / or the second part of the mixture according to (a) comprises fibers. Preferably, the fibers are contained in the first part and the second part. The same applies to the expression "the fibers are applied simultaneously to the surface of the three-dimensional body of the layered mineral material in (c.1) and / or in (c.3)", i.e. glass fibers are applied in (c.1) and / or in (c.3). Preferably, in both steps (c.1) and (c.3), the fibers are applied simultaneously to the surface of the three-dimensional body of the layered mineral material. "Simultaneous application" means, for example, that the fibers are mixed in situ into the first part and / or the second part of the mixture according to (a), wherein, for example, the fibers are dripped into a spray nozzle, with which the first part and / or the second part of the mixture according to (a) are applied.
[0172] Regarding steps (c.2) and (c.3), preferably, the first polyurethane layer is partially cured, i.e. the viscosity of the first polyurethane layer has increased, and when the second part of the mixture according to (a) is applied in (c.3), i.e. when the second layer of the mixture is formed on the first polyurethane layer, there is still an ongoing reaction of the isocyanate groups with the OH groups.
[0173] In some preferred embodiments of the method according to the second aspect or the third aspect, the layered mineral material has undergone a pretreatment, wherein the surface of the pretreated layered mineral material is rougher than the surface of the layered mineral material before the pretreatment, wherein the pretreatment is preferably selected from the group consisting of: sandblasting, roughening (for example by using coarse-grained sandpaper) and a mixture of two or more of these pretreatments.
[0174] Furthermore, any additional or alternative pre-treatment is suitable, which reduces the adhesion between the individual layers of the layered mineral material. Suitable pre-treatments for reducing adhesion are known to the person skilled in the art.
[0175] Aspect 4 - Laminate
[0176] In a fourth aspect, the present invention relates to a laminate obtained or obtainable by the method according to the third aspect as described in detail above or the method according to the fourth aspect.
[0177] In some embodiments, the above laminates are attached to a carrier, including post-processing / finishing, optionally pre-treating the laminate such as by flame treatment, plasma or corona, adding adhesives, curing the multilayer laminate (optionally at above room temperature).
[0178] In some embodiments, the above-mentioned laminate is attached to a carrier, including post-treatment / finishing, optionally, for example, by flame treatment, plasma or corona pretreatment of the laminate, the laminate is inserted into a mold or inserted into a continuous production line, a resin (optionally expandable resin) is added, and the multilayer laminate is cured (optionally cured at higher than room temperature). According to the measurement of VDA278:2016-05, the laminate contains only a small amount of <1000ppm, preferably <500ppm of volatile organic matter (VOC), and in addition, according to VDA278:2016-05, the laminate contains a small amount of <1000ppm of semi-volatile fogging compounds (FOG). In contrast, as used in EP 3 785 900 A1, according to the safety data sheet, the polyol composition of "PU NEUKADUR PN 9712 2-C polyurethane adhesive" has a VOC of 44000ppm measured according to VDA278:2016-05.
[0179] Aspect 5 - Purpose
[0180] A fifth aspect of the present invention relates to the use of the laminate according to the first aspect or the laminate according to the fourth aspect for wall panels, roof panels, facings, wallpapers, kitchen surfaces, shower enclosures, clothes, shoes, bags, automotive interior parts, battery parts, general furniture, sofas, outdoor furniture, and decorative items.
[0181] The present invention is further illustrated by the following groups of embodiments and combinations of embodiments resulting from the indicated dependencies and back-references. In particular, it should be noted that in each case where a range of embodiments is mentioned, for example in the context of terms such as "any one of embodiments (1) to (4)", each embodiment within the range refers to being explicitly disclosed by a person skilled in the art, i.e., the wording of the term should be understood by the skilled person as being synonymous with "any one of embodiments (1), (2), (3) and (4)". In addition, it should be explicitly pointed out that the following group of embodiments is not a group of claims for determining the scope of protection, but rather an appropriate structural part of the description of general aspects and preferred aspects of the present invention.
[0182] 1. A laminate comprising at least one layer of a laminar mineral material and a polyurethane layer, wherein the polyurethane of the polyurethane layer is obtained or is obtainable from a mixture comprising the following components:
[0183] (i) a polyisocyanate composition;
[0184] (ii) a polyol composition, the polyol composition comprising
[0185] (iia) at least one non-polar polyester polyol having an average electronegativity difference ΔEN<0.38, wherein ΔEN is the sum of the electronegativity differences (δEN) of all bonds in the non-polar polyester polyol divided by the total number of bonds in the non-polar polyester polyol.
[0186] 2. A laminate according to embodiment 1, wherein the water absorption of the non-polar polyester polyol (iia) is <0.4 wt.-%, preferably <0.35 wt.-%, based on the total weight of the non-polar polyester polyol (iia), and / or the water absorption of the polyol composition (ii) is <0.45 wt.-%, preferably <0.4 wt.-%, based on the total weight of the polyol composition (ii), wherein the values for the water absorption are in each case determined according to Reference Example 5.
[0187] 3. The laminate according to embodiment 1 or 2, wherein the mixture comprises ≥ 8 wt% of the at least one non-polar polyester polyol (iia), based on 100 wt% of the total weight of (i) and (ii).
[0188] 4. A laminate according to any one of embodiments 1 to 3, wherein the average electronegativity difference ΔEN of the at least one non-polar polyester polyol (iia) is <0.35, preferably <0.33, wherein ΔEN is the sum of the electronegativity differences (δEN) of all bonds in the non-polar polyester polyol divided by the total number of bonds in the non-polar polyester polyol.
[0189] 5. The laminate according to any one of embodiments 1 to 4, wherein the hydroxyl value of the polyol composition (ii) is in the range of 150 mg KOH to 500 mg KOH per gram of the sum of all liquid components of the polyol (ii).
[0190] 6. The laminate of any one of embodiments 1 to 5, comprising fibers embedded in the polyurethane layer.
[0191] 7. A laminate according to embodiment 6, wherein the fibers are textiles or short-cut fibers, wherein the textiles include woven textiles or nonwoven textiles or knitted textiles or non-wrinkled textiles and combinations of two or more thereof, wherein the area weight of the textiles is preferably <300 g / m 2 , more preferably <200g / m 2 , more preferably at 20g / m 2 Up to 175g / m 2 In the range of 30 g / m 2 Up to 150g / m 2 The average length of the chopped fibers is in the range of 1 mm to 10 mm, preferably 2 mm to 6 mm, and the diameter is 10 μm to 15 μm.
[0192] 8. A laminate according to any one of embodiments 1 to 7, wherein the mixture comprising components (i) and (ii) comprises >7% bio-based carbon determined according to ASTM D6866-21, relative to 100% total carbon in the mixture; and comprises preferably in the range of 7.5% to 60%, more preferably in the range of 8.5% to 50%, determined according to ASTM D6866-21, relative to 100% total carbon in the mixture, preferably determined according to Reference Example 4.
[0193] 9. The laminate according to any one of embodiments 1 to 8, wherein the mixture further comprises:
[0194] (iib) Dispersions comprising solid fillers and preferably polyether polyols and / or additionally polyester polyols.
[0195] 10. The laminate according to embodiment 9, wherein the filler is selected from TiO2, carbon black, graphite, zeolite and a mixture of two or more of these fillers.
[0196] 11. A laminate according to any one of embodiments 1 to 10, wherein the isocyanate composition according to (i) comprises a polyisocyanate, preferably a diisocyanate, more preferably a (di)isocyanate obtained or obtainable from a diisocyanate and a polyether polyol.
[0197] 12. The laminate according to any one of embodiments 1 to 11, wherein the at least one non-polar polyester polyol (iia) contains polyether units in the range of zero wt% to 25 wt%, based on the total weight of the at least one non-polar polyester polyol (iia).
[0198] 13. The laminate according to any one of embodiments 1 to 12, wherein the content of the polyester polyol units is > 20 wt.-%, based on the total weight of all liquid components present in (i) and (ii).
[0199] 14. The laminate according to any one of embodiments 1 to 13, wherein the polyisocyanate composition (i) and / or the polyol composition (ii) comprises one or more liquid and / or solid flame retardants.
[0200] 15. The laminate according to any one of embodiments 1 to 14, wherein the polyol composition (ii) comprises at least 1 ppm of iron (in the form of iron cations).
[0201] 16. A laminate according to any one of embodiments 1 to 15, wherein the layered mineral material is preferably a layered natural stone, more preferably selected from the group consisting of slate, mica, graphite, mica rock, layered silicates (such as carbon siliceous calcium calcium stone, kaolin, talc), montmorillonite, molybdenum (IV) sulfate and a mixture of two or more of these layered mineral materials, wherein the layered mineral material preferably contains at least slate, more preferably consists of slate.
[0202] 17. A laminate according to any one of embodiments 1 to 16, wherein the layered mineral material is cut parallel to its layered structure, and wherein the roughness R of the mineral surface intended for producing the laminate is a (arithmetic mean height according to ISO 25178, measured according to DIN EN ISO 4287:2010-07 by means of a laser scanning microscope Keyence VK-X3000) greater than 1.5 μm, in particular greater than 2 μm.
[0203] 18. The laminate according to any one of embodiments 1 to 17, wherein the area weight of the laminate is 500 g / mm 2 Up to 1800g / mm 2In the range of 900 g / mm 2 Up to 1500g / mm 2 within the range.
[0204] 19. The laminate according to any one of embodiments 1 to 18, having a thickness of less than 2 mm, preferably less than 1.5 mm, more preferably in the range of 0.5 mm to 1.0 mm, more preferably in the range of 0.7 mm to 0.9 mm.
[0205] 20. The laminate according to any one of embodiments 1 to 18, having a thickness less than 0.3 mm, preferably in the range of 0.1 mm to 0.3 mm.
[0206] 21. A method for preparing a laminate, wherein the laminate comprises layers of a layered mineral material and at least one polyurethane layer, the method comprising:
[0207] (a) providing components for a mixture, the mixture comprising at least:
[0208] (i) a polyisocyanate composition;
[0209] (ii) a polyol composition comprising at least one non-polar polyester polyol (iia) having an average electronegativity difference ΔEN<0.38, wherein ΔEN is the sum of the electronegativity differences (δEN) of all bonds in the non-polar polyester polyol divided by the total number of bonds in the non-polar polyester polyol,
[0210] and mixing (i) and (ii) to form a mixture;
[0211] (b) providing a three-dimensional body of layered mineral material;
[0212] (c) applying a first layer of the mixture according to (a) onto a surface of the three-dimensional body of layered mineral material, wherein the surface is oriented substantially parallel to the layer of the layered mineral material, thereby forming a layer of the mixture on the surface;
[0213] (d) applying a second layer of the mixture according to (a) on top of the first layer;
[0214] (e) optionally applying a third layer of said mixture according to (a) on top of said second layer, thereby forming an at least partially uncured laminate;
[0215] (f) curing the laminate obtained in (e) at a temperature optionally above room temperature.
[0216] 22. A method for preparing a laminate, wherein the laminate comprises layers of a layered mineral material and at least one polyurethane layer, the method comprising:
[0217] (a) providing components for forming a mixture, the mixture comprising at least:
[0218] (i) a polyisocyanate composition;
[0219] (ii) a polyol composition comprising at least one non-polar polyester polyol (iia) having an average electronegativity difference ΔEN<0.38, wherein ΔEN is the sum of the electronegativity differences (δEN) of all bonds in the non-polar polyester polyol divided by the total number of bonds in the non-polar polyester polyol,
[0220] and mixing (i) and (ii) to form a mixture;
[0221] (b) providing a three-dimensional body of layered mineral material;
[0222] (c) applying a first layer of the mixture according to (a) onto a surface of the three-dimensional body of layered mineral material, wherein the surface is oriented substantially parallel to the layer of the layered mineral material, thereby forming a layer of the mixture on the surface;
[0223] (d) reacting (i) and (ii) of the mixture, thereby forming a polyurethane layer on the surface of the three-dimensional body of layered mineral material, the polyurethane layer being at least partially connected to at least the first layer of the layered mineral material;
[0224] (e) applying a second layer of the mixture according to (a) on top of the polyurethane layer formed in (d),
[0225] (f) applying a textile layer on top of the second layer and applying a force to embed the textile layer, wherein the applied force is preferably 2.5 N / mm 2 Up to 30N / mm 2 within the scope of
[0226] (g) optionally applying a third or more layers of the mixture according to (a) on top of the embedded textile layer of (f); thereby forming an at least partially uncured laminate;
[0227] (h) optionally curing the laminate at a temperature above room temperature.
[0228] 23. The method according to embodiment 21 or 22, comprising:
[0229] (i) Removing the solidified laminate formed in (f) of Embodiment 21 or (h) of Embodiment 22 from a three-dimensional body of a layered mineral material, followed by also removing at least the first layer of the layered mineral material, thereby obtaining a (separated) laminate.
[0230] 24. The method of any one of embodiments 21 to 23, wherein (c) comprises:
[0231] (c.1) applying a first portion of the mixture according to (a) onto a surface of the three-dimensional body of layered mineral material, wherein the surface is oriented substantially parallel to the layers of the layered mineral material, thereby forming a first layer of the mixture on the surface;
[0232] (c.2) optionally at least partially reacting (i) and (ii) of the first part of the mixture, thereby forming a first polyurethane layer on the surface of the three-dimensional body of layered mineral material, the first polyurethane layer being at least partially connected to at least the first layer of the layered mineral material;
[0233] (c.3) applying a second portion of the mixture according to (a) onto the first polyurethane layer formed in (c.2), thereby forming a second layer of the mixture on the first polyurethane layer;
[0234] wherein the second part and / or the first part of the mixture according to (a) comprises fibers, or wherein in (c.1) and / or (c.3) fibers are simultaneously applied to the surface of the three-dimensional body of layered mineral material;
[0235] wherein (d) comprises reacting (i) and (ii) of the first and second parts of the mixture, thereby forming a polyurethane layer on the surface of the three-dimensional body of layered mineral material, the polyurethane layer being at least partially connected to at least the first layer of the layered mineral material.
[0236] 25. A method according to any one of embodiments 21 to 24, wherein the layered mineral material has undergone pretreatment, wherein the surface of the pretreated layered mineral material is rougher than the surface of the layered mineral material before pretreatment, wherein the pretreatment is preferably selected from the group consisting of: sandblasting, roughening (for example by using coarse-grained sandpaper) and a mixture of two or more of these pretreatments.
[0237] 26. A laminate obtained or obtainable by the method according to any one of embodiments 20 to 25.
[0238] 27. Use of the laminate according to any one of embodiments 1 to 19 or the laminate according to embodiment 26 for wall panels, roof panels, facings, wallpapers, kitchen surfaces, shower enclosures, clothes, shoes, bags, automotive interior parts, battery parts, general furniture, sofas, outdoor furniture, decorations.
[0239] The present invention is further illustrated by the following reference examples, comparative examples and embodiments. Example
[0240] Material
[0241]
[0242]
[0243] *ΔEN: average electronegativity difference of the polyols determined according to equation (1):
[0244]
[0245] in
[0246] ΔEN is the average electronegativity difference of the polyols,
[0247] δEN is the electronegativity difference of the atoms of the bonds in the polyol (according to the Allred-Rochow scale), and n is the number of all bonds in the polyol.
[0248] ** Determined according to Reference Example 5
[0249] 2. Test Method
[0250] Hydroxyl value (OH value, OHZ): DIN 53240-2016-03
[0251] NCO value: Titration according to DIN EN ISO 14896-2009-07
[0252] Water content: Titration according to DIN EN ISO 8534:2017-05 (Karl-Fischer)
[0253] Kinematic viscosity: ASTM D445-21 (25°C)
[0254] Ratio of organic (i.e. biobased) carbon to total carbon: ASTM D6866-21 or ISO 16620-2-2019-10
[0255] SBI (Single Combustion Project): DIN EN 13823-2020-09
[0256] Particle size distribution ISO 13320:01 2020
[0257] Laboratory test to determine laminate density or area weight of textiles: Cut a rectangular specimen from a larger laminate or textile, measure the x, y, and z dimensions with calipers, and weigh the specimen or textile.
[0258] According to the composition shown in Table 1, the corresponding polyol and isocyanate components were prepared respectively using a Vollrath agitator and the polyol component was blended at 1500 rpm for at least 300 s. In the next step, the polyol component was blended with the isocyanate component in a cup at 1500 rpm for 10 s. The reaction mixture was poured into a small cup (Greiner) until the cup was completely filled. When the resulting polyurethane (PU) was solid, the weight and volume were determined to calculate the pure PU density.
[0259] Study on dispersion stability
[0260] A drop of the dispersion was placed on a glass slide for microscopy studies. An Olympus Stereo microscope SZX12 was used at maximum magnification. The images were visually analyzed with regard to particle size (if larger than 1 μm) and potential aggregation.
[0261] Reference Example 1 Method A: Sample preparation by hand lamination
[0262] The slate block was cut into dimensions of 25 cm x 50 cm x 1 cm parallel to the slate layer. The slate block was mechanically cleaned with a metal brush and then subjected to compressed air treatment. Polyethylene tape was attached to the edges of the slate block to form a frame with a height of about 1 mm around the slate block. A nonwoven textile (glass mat, weight 150 g / m2 , Oschatz) into rectangular sheets of about 30 cm in length and about 55 cm in width. Polyethylene (PE) tape is applied to both surfaces of the nonwoven rectangular sheet in the textile edge area to 25 cm×50 cm, so that the edge area is covered by the PE tape.
[0263] According to the composition shown in Table 1 below, a Vollrath agitator is used and the polyol component containing polyol and any other components except isocyanate is blended at least 300s at 1500rpm to prepare the corresponding polyol and isocyanate components respectively. In the next step, the polyol component is blended at 1500rpm for 10s with the isocyanate component containing isocyanate. The reaction mixture (which should produce 55g PU / layer) is poured on a plow floor plate on a plane with a size of 25cm×50cm and evenly distributed using a roller. After a waiting time of 30 minutes, another layer of reaction mixture is added and evenly distributed with the aid of a roller. Then, a rectangular sheet (25cm×50cm) of nonwoven textiles is applied on top of the reaction mixture. By using a Teflon roller, the textile is pressed into the resin in a wrinkle-free manner and the air is pressed out. The device is cured at room temperature for 24 hours, so that the reaction mixture forms a polyurethane (PU) layer. After curing, grab the loose end of the textile near the corner (the edge area coated with PE tape) and carefully pull it out from the slate along the 25cm side, which also peels off the slate layer adhered to the PU. The laminate of the non-woven textile, the PU layer and the slate layer adhered to it is called a "laminate". The first centimeter of the laminate is manually pressed on a tube with a diameter of 15cm. The tube is rolled slowly and evenly to remove the entire laminate from the slate block. After trimming and optionally curing for 3 hours at 100°C, the laminate is ready for attaching additional materials. In order to prepare the front element, the PU side of the laminate is cleaned with compressed air. Then pour water glass or acrylate adhesive on the PU surface and evenly distribute it. Make an 8mm thick fibrous concrete sheet contact and adhesively bond with the adhesive. The curing time is 7 days at room temperature.
[0264] Reference Example 2: Method B: Sample preparation by spray coating
[0265] The slate block was cut into a size of 25 cm × 50 cm × 1 cm parallel to the slate layer. The slate block was mechanically cleaned with a metal brush and then subjected to compressed air treatment. Polyethylene tape was attached to the edge of the slate block to form a frame with a height of about 1 mm around the slate block. Woven textiles (Lange + Ritter type 1080; mesh) were cut into rectangles with a size of 30 cm × 55 cm. Polyethylene (PE) tape was applied to both surfaces of the rectangular piece in the edge area so that the edge area was covered by the PE tape. According to the composition shown in Table 1, a Vollrath stirrer was used and each component was blended at 1500 rpm for a minimum of 300 s to prepare the corresponding polyol and isocyanate components respectively. The polyol and isocyanate components were filled into the tank of the high-pressure sprayer. Sample preparation was carried out in a ventilated spray room. The reaction mixture containing polyols and isocyanates was sprayed on the top of the slate block in the gallery. After a waiting time of 20 minutes, the second layer was sprayed in the gallery. The prepared textile is then pressed into the reaction mixture and the already formed / forming polyurethane (PU) resin in a wrinkle-free manner. The device is cured for 24 hours at room temperature. After curing, the loose end of the textile is grasped near the corner (the edge area coated with the PE tape) and carefully pulled out from the slate along the 25 cm side, which also peels off the slate layer adhering to the PU. The laminate of the woven textile, the PU layer and the slate layer adhered thereto is called a "laminate". The first centimeter of the laminate is manually pressed on a tube with a diameter of 15 cm. The tube is rolled slowly and evenly to remove the entire laminate from the slate block. After trimming and optionally curing for 3 hours at 100 ° C, the laminate is ready for attachment of additional materials.
[0266] Reference Example 3: Method C: Sample preparation by spray coating
[0267] The polyol component was prepared in the same manner as in method B. In addition, 2 wt% of glass fiber powder (P316-14C Lange & Ritter, 3 mm average length) was mixed into the polyol component. Then, a polyurethane resin was prepared in the same manner as in method B and applied to the slate. In method C, no textile was added to the reaction mixture. The device was cured at room temperature for 24 hours. Then, the laminate comprising only the PU layer and the slate layer was removed from the slate block in the same manner as in method B. After trimming and optionally after curing at 100° C. for 3 hours, the laminate was ready for attachment of additional materials.
[0268] Reference Example 4: Determination of the ratio of bio-based carbon to total carbon
[0269] The ratio of biobased carbon to total carbon (C) is determined as follows:
[0270] 1) Calculate the chemical composition (recipe) of each raw material based on the composition of all ingredients.
[0271] 2) Calculate the total carbon content of the raw materials.
[0272] 3) Determine based on specific molecular composition which substructures are synthesized based on renewable raw materials (bio-based) and which substructures are based on petrochemicals.
[0273] 4) The total carbon content and the percentage of carbon of petrochemical origin and carbon of biological origin (biobased carbon) of each example were calculated based on the feedstock data, and then the ratio of biobased carbon to total carbon was determined.
[0274] Calculations were performed at the level of the A component as well as the A+B component.
[0275] Reference Example 5: Determination of water absorption
[0276] 100g of a mixture containing 96.8 wt% polyol, 3 wt% additive 1 and 0.2 wt% additive 2 was stored in a cylindrical polypropylene cup (6.5 cm diameter) at 30 ° C, 70% humidity for 1 hour. Subsequently, humidity was measured according to DIN EN ISO8534:2017-05. In the case of a polyol mixture, a 100g mixture containing 96.8 wt% polyol mixture (comprising two or more polyols), 3 wt% additive 1 and 0.2 wt% additive 2 was stored at 30 ° C, 70% humidity for 1 hour. Subsequently, humidity was measured according to DIN EN ISO 8534:2017-05. In order to determine the water absorption of the polyol component A listed in Table 1 below, 100g of polyol component A [corresponding to polyol component (ii)] was stored in an open cylindrical PP cup (6.5 cm diameter) for 1 hour at 30 ° C, 70% humidity. The cup was then sealed and the water content was measured by Karl-Fischer titration according to DIN EN ISO 8534:2017-05.
[0277] Comparative Examples and Examples
[0278] Comparative Examples 1 to 3 and Inventive Examples 1 to 4 were prepared according to the procedures described above in Reference Examples 1 to 3, and the compositions, procedures and resulting properties are listed in Table 1. Portions of the polyols shown in Table 1 are "biobased", i.e. these polyols or portions thereof are obtained by fermentation, by enzymatic modification or chemical modification of a base bioproduct.
[0279]
[0280]
[0281]
[0282]
[0283] Regarding the ratio of bio-based carbon content to total C, the ratio of bio-based carbon to total carbon of the comparative examples based on polyether polyols is in the range of 10% to 12% (A component). The corresponding values of the examples of the present invention are in the range of 49% to 51% (filled systems, Examples 1 to 3) and 50% to 75% (unfilled systems, Examples 4 and 5).
[0284] When calculated based on the total amount of resin (A+B components), the ratio of bio-based to total carbon ranged from 5% to 7.5% for the comparative examples, and ranged from 27% to 28% (filled systems, Examples 1 to 3) and from 38% to 44% (unfilled systems, Examples 4 and 5), respectively.
[0285] It was observed that the formulation based on polyether polyols without fillers (Comparative Example 1) produced strong foaming. Thus, a layer of the composition / reaction mixture applied with a thickness of 1 mm produced a thickness of 5 mm after curing. Due to the cohesive failure in the PU foam layer, it was not possible to remove the laminate with slate. If CaCO3 was added to the same formulation (Comparative Example 2), there was less foaming and it was not possible to remove the laminate with slate. Adhesion failure between slate and PU layer was observed. If the dispersion was changed, no difference was observed (Comparative Example 3).
[0286] Different formulation concepts based on hydrophobic polyetherester polyols lead to the successful removal of laminates having PU layers and slate layers after complete curing, both with and without fillers (Examples 1 to 5).
[0287] Example 6: Effect of surface roughness of layered mineral materials .
[0288] 3 pieces of slate were used for sample preparation. At the beginning, the roughness Ra of the slate sample was measured (arithmetic mean height according to ISO 25178, measured by laser scanning microscope Keyence VK-X3000 according to DIN EN ISO 4287-2010-07).
[0289] Sample A, untreated: surface roughness Ra = 3.76 μm (generated by analyzing 5 points on a 4000 μm sample)
[0290] Sample B, after rough polishing: surface roughness Ra = 1.94 μm (generated by analyzing 5 points on a sample of 4000 μm size)
[0291] Sample C, after fine polishing: surface roughness Ra = 1.12 μm (generated by analyzing 5 points on a sample of 4000 μm size)
[0292] All laminates were prepared using the recipe of Example 1 and Method A. After preparation, the thickness of the slate layer was measured by microscopic analysis: Sample A: 80 μm slate layer, Sample B: 35 μm slate layer, Sample C: 15 μm slate layer.
[0293] Example 7: Determining the Flexibility or Stiffness of a Laminate
[0294] Several slate laminates were prepared according to Example 4 and Method A (F2 to F6) and Example 4 and Method B (F1). The samples were cut into strips and then subjected to cantilever bending length testing according to ASTM D1388 (October 2018). At 20 cm overhang length, the overhang height was measured.
[0295] Table 3
[0296] Overhang of selected laminate
[0297] sample Laminate thickness Overhang height Plough bottom plate, 8mm - 0.0cm Sample F1 0.2mm 19.4cm Sample F2 0.5mm 12.6cm Sample F3 0.5mm 14.0cm Sample F4 1mm 3.8cm Sample F5 0.5mm 18.4cm Sample F6 0.5mm 18.0cm Sample F7 1mm 3.7cm Sample F8 1mm 4.4cm Sample F9 2mm 1.7cm Sample F10 1mm 1.6cm Sample F11 2mm 1.7cm Sample F12 2mm 1.3cm Sample F13 2mm 1.7cm Sample F14 2mm 1.1cm Sample F15 4mm 3.3cm Sample F16 1.5mm 1.5mm Sample F17 1mm 1.8mm Sample F18 2mm 1.2mm
[0298] The overhang height depends on the pretreatment, the composition of the laminate (fibers, fiber length, etc.), the thickness of the laminate, and of course on the properties of the layered material. Since slate and other layered mineral materials are natural materials, their properties can vary and depend largely on the location where they are collected. Slate and layered mineral materials differ, for example, in composition, color, homogeneity, impurities, crystallinity, maximum block size, depending on their origin. However, it was shown that the overhang height was always at least>1 cm. Therefore, all tested laminates can be considered as bendable laminates.
[0299] References
[0300] -US 3,287,197
[0301] -DE 19522875 A1
[0302] -EP 3 785 900 A1
[0303] -ALAllred, EGRochow: A scale of electronegativity based on electrostatic force. "Journal of Inorganic and Nuclear Chemistry", 1958, DOI10.1016 / 0022-1902(58)80003-2
[0304] -A.L. Allred: "Electronegativity values from thermochemical data." Journal of Inorganic and Nuclear Chemistry, 1961, DOI 10.1016 / 0022-1902(61)80142-5)
[0305] -US 2006 / 041156 A1
[0306] -US 4,742,087 A
[0307] -US 6,730,768 B2
[0308] -M. Ionescu, Chemistry and Technology of polyols for polyurethanes, iSmithers Rapra Publishing, 2005, Chapter 17, Polyols from renewable resources - oleochemical polyols
[0309] - "Plastics Handbook, 7, Polyurethanes", Carl Hanser-Verlag, 3rd Edition, 1993, Chapter 3.1
[0310] - "Plastics Handbook, 7, Polyurethanes", Carl Hanser-Verlag, 3rd Edition, 1993, Chapters 3.4.4 and 3.4.6 to 3.4.11.
Claims
1. A laminate comprising at least one layer of a laminar mineral material and a polyurethane layer, wherein the polyurethane of the polyurethane layer is obtained or is obtainable from a mixture comprising the following components: (i) a polyisocyanate composition; (ii) a polyol composition, the polyol composition comprising (iia) at least one non-polar polyester polyol having an average electronegativity difference ΔEN<0.38, wherein ΔEN is the sum of the electronegativity differences (δEN) of all bonds in the non-polar polyester polyol divided by the total number of bonds in the non-polar polyester polyol.
2. A laminate according to embodiment 1, wherein the water absorption of the non-polar polyester polyol (iia) is <0.4 wt.-%, preferably <0.35 wt.-%, based on the total weight of the non-polar polyester polyol (iia), and / or the water absorption of the polyol composition (ii) is <0.45 wt.-%, preferably <0.4 wt.-%, based on the total weight of the polyol composition (ii), wherein the values for the water absorption are in each case determined according to Reference Example 5.
3. The laminate according to any one of claims 1 or 2, wherein the at least one non-polar polyester polyol (iia) has an average electronegativity difference ΔEN <0.35, preferably <0.33, wherein ΔEN is the sum of the electronegativity differences (δEN) of all bonds in the non-polar polyester polyol divided by the total number of bonds in the non-polar polyester polyol. 4 . The laminate according to claim 1 , wherein the hydroxyl value of the polyol composition (ii) is in the range of 150 to 500 mg KOH per gram of the sum of all liquid components of the polyol (ii).
5. A laminate according to any one of claims 1 to 4, comprising fibres embedded in the polyurethane layer.
6. The laminate according to claim 5, wherein the fibers are textiles or chopped fibers, wherein the textiles include woven textiles or nonwoven textiles or knitted textiles or non-wrinkled textiles and combinations of two or more thereof, wherein the area weight of the textiles is preferably <300 g / m 2 , more preferably <200g / m 2 , more preferably at 20g / m 2 Up to 175g / m 2 In the range of 30 g / m 2 Up to 150g / m 2 The average length of the chopped fibers is in the range of 1 mm to 10 mm, preferably 2 mm to 6 mm. and a diameter of 10 μm to 15 μm.
7. A laminate according to any one of claims 1 to 6, wherein the mixture comprising the components (i) and (ii) comprises >7% bio-based carbon determined according to ASTM D6866-21, relative to 100% total carbon in the mixture; preferably comprises bio-based carbon in the range of 7.5% to 60%, more preferably in the range of 8.5% to 50%, relative to 100% total carbon in the mixture, determined according to ASTM D6866-21, preferably determined according to Reference Example 4.
8. The laminate according to any one of claims 1 to 7, wherein the mixture further comprises: (iib) A dispersion comprising a solid filler and preferably a polyether polyol and / or an additional polyester polyol; wherein the filler is preferably selected from the group consisting of TiO2, carbon black, graphite, zeolite and mixtures of two or more of these fillers.
9. The laminate according to any one of claims 1 to 8, wherein the at least one non-polar polyester polyol (iia) contains polyether units in the range of zero wt% to 25 wt%, based on the total weight of the at least one non-polar polyester polyol (iia).
10. The laminate according to any one of claims 1 to 9, wherein the mixture comprises ≥ 8 wt.-% of the at least one non-polar polyester polyol (iia), based on 100 wt.-% of the total weight of (i) and (ii), and / or wherein the content of polyester polyol units is > 20 wt.-%, based on the total weight of all liquid components present in (i) and (ii).
11. A laminate according to any one of claims 1 to 10, wherein the layered mineral material is preferably a layered natural stone, more preferably selected from the group consisting of slate, mica, graphite, mica rock, layered silicates (e.g., calcite, kaolin, talc), montmorillonite, molybdenum (IV) sulfate and a mixture of two or more of these layered mineral materials, wherein the layered mineral material preferably contains at least slate, more preferably consists of slate.
12. A method for preparing a laminate, wherein the laminate comprises layers of a layered mineral material and at least one polyurethane layer, the method comprising: (a) providing components for a mixture, the mixture comprising at least: (i) a polyisocyanate composition; (ii) a polyol composition comprising at least one non-polar polyester polyol (iia) having an average electronegativity difference ΔEN<0.38, wherein ΔEN is the sum of the electronegativity differences (δEN) of all bonds in the non-polar polyester polyol divided by the total number of bonds in the non-polar polyester polyol, and mixing (i) and (ii) to form a mixture; (b) providing a three-dimensional body of layered mineral material; (c) applying a first layer of the mixture according to (a) onto a surface of the three-dimensional body of layered mineral material, wherein the surface is oriented substantially parallel to the layer of the layered mineral material, thereby forming a layer of the mixture on the surface; (d) applying a second layer of the mixture according to (a) on top of the first layer; (e) optionally applying a third layer of said mixture according to (a) on top of said second layer, thereby forming an at least partially uncured laminate; (f) curing the laminate obtained in (e) optionally at a temperature above room temperature.
13. A method for preparing a laminate, wherein the laminate comprises layers of a layered mineral material and at least one polyurethane layer, the method comprising: (a) providing components for forming a mixture, the mixture comprising at least: (i) a polyisocyanate composition; (ii) a polyol composition comprising at least one non-polar polyester polyol (iia) having an average electronegativity difference ΔEN<0.38, wherein ΔEN is the sum of the electronegativity differences (δEN) of all bonds in the non-polar polyester polyol divided by the total number of bonds in the non-polar polyester polyol, and mixing (i) and (ii) to form a mixture; (b) providing a three-dimensional body of layered mineral material; (c) applying a first layer of the mixture according to (a) onto a surface of the three-dimensional body of layered mineral material, wherein the surface is oriented substantially parallel to the layer of the layered mineral material, thereby forming a layer of the mixture on the surface; (d) reacting (i) and (ii) of the mixture, thereby forming a polyurethane layer on the surface of the three-dimensional body of layered mineral material, the polyurethane layer being at least partially connected to at least the first layer of the layered mineral material; (e) applying a second layer of the mixture according to (a) on top of the polyurethane layer formed in (d), (f) applying a textile layer on top of the second layer and applying a force to embed the textile layer, wherein the applied force is preferably 2.5 N / mm 2 Up to 30N / mm 2 within the scope of (g) optionally applying a third or more layers of the mixture according to (a) on top of the embedded textile layer of (f); thereby forming an at least partially uncured laminate; (h) optionally curing the laminate at a temperature above room temperature.
14. A laminate obtained or obtainable by the method according to claim 12 or 13.
15. Use of the laminate according to any one of claims 1 to 11 or the laminate according to claim 14 for wall panels, roof panels, facings, wallpapers, kitchen surfaces, shower enclosures, clothes, shoes, bags, car interior parts, battery parts, general furniture, sofas, outdoor furniture, decorations.
Citation Information
Patent Citations
Flexible sheet material
DE19522875A1
Lightweight stone product
EP3785900A1
Methods of preparing hydroxy functional vegetable oils
US20060041156A1
Process for permanently cladding an inorganic surface with plastic and product made thereby
US3287197A
Polyurethane prepolymers based on oleochemical polyols, their production and use
US4742087A